1993
DOI: 10.3171/jns.1993.79.4.0483
|View full text |Cite
|
Sign up to set email alerts
|

Increased stroke risk predicted by compromised cerebral blood flow reactivity

Abstract: The authors sought to determine risk for stroke in individuals with symptomatic carotid stenosis or occlusion based upon an assessment of cerebral blood flow (CBF) reserves. Vascular reserve was assessed by two consecutive xenon/computerized tomography (Xe/CT) CBF studies with intravenous acetazolamide introduced 20 minutes prior to the second study. Patients were assigned to one of two vasoreactivity groups. Group 2 included individuals who experienced a CBF reduction of more than 5% in at least one vascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
238
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 457 publications
(245 citation statements)
references
References 29 publications
5
238
0
2
Order By: Relevance
“…Recently it was shown that a diminished CVR is a predictor of stroke in patients with symptomatic carotid artery occlusive disease (16). Furthermore, cerebral periventricular white matter lesions have been found to be correlated with decreased vasomotor reactivity in asymptomatic individuals (17), increased stroke risk (18), first-ever lacunar infarction (19), and deep white matter lesions (20). Apart from responding to hypercapnia, hypoxia, and hypotension, the CVR may also be challenged pharmacologically.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it was shown that a diminished CVR is a predictor of stroke in patients with symptomatic carotid artery occlusive disease (16). Furthermore, cerebral periventricular white matter lesions have been found to be correlated with decreased vasomotor reactivity in asymptomatic individuals (17), increased stroke risk (18), first-ever lacunar infarction (19), and deep white matter lesions (20). Apart from responding to hypercapnia, hypoxia, and hypotension, the CVR may also be challenged pharmacologically.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that intrasubject flow CVR as measured by ASL is affected by PO 2 and is not consistent between CO 2 in air and carbogen. Although the possibility remains that this inconsistency could be a result of imperfect estimation of tissue pressure of CO 2 and CBF under a combined hyperoxia and hypercapnia regime, particular care should be taken when comparing flow CVR values obtained from stimuli containing different fractions of oxygen. …”
Section: Arterial Spin Labeling and Carbogenmentioning
confidence: 99%
“…1,3 Impaired CVR is a predictor for increased risk of ipsilateral stroke and transient ischemic attack (TIA) in patients with steno-occlusive carotid disease. 4,5 Similarly, increased OEF has been shown to predict recurrent ischemic stroke in patients with symptomatic occlusive disease of the cerebral vasculature. 6 Furthermore, a higher stroke risk has been observed in patients with impaired CVR and increased OEF when compared with patients with impaired CVR only.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, perfusion or flow techniques combined with a vasodilatory stimulus have been proposed to evaluate the CVR. Invasive techniques such as xenon-enhanced computed tomography 5 or noninvasive techniques such as Doppler ultrasonography, 4 blood oxygen level-dependent (BOLD) magnetic resonance imaging (MRI), 9 or arterial spin labeling MRI 10 have been suggested. A dualecho arterial spin labeling (ASL) sequence can acquire perfusion data (first echo) and BOLD data (from the second echo which has T 2 * weighting) simultaneously.…”
Section: Introductionmentioning
confidence: 99%